The idea factory bell labs and the great age of American innovation - Gertner, Jon (New York Penguin Books, 2013)
Highlights achievements of Bell Labs as a leading innovator, exploring the role of its highly educated employees in developing new technologies while considering the qualities of companies where innovation and development are most successful
Keywords: Bell Telephone Laboratories -- History -- 20th century; Telecommunication -- United States -- History -- 20th century; Technological innovations -- United States -- History -- 20th century; Creative ability -- United States -- History -- 20th century; Inventors -- United States -- History -- 20th century